Impact of blood glucose, diabetes, insulin, and obesity on standardized uptake values in tumors and healthy organs on 18F-FDG PET/CT - Büsing, Karen-Anett; Schönberg, Stefan; Brade, Joachim; Wasser, Klaus (Nuclear medicine and biology, 2013)
Introduction Chronically altered glucose metabolism interferes with 18F-FDG uptake in malignant tissue and healthy organs and may therefore lower tumor detection in 18F-FDG PET/CT. The present study assesses the impact of elevated blood glucose levels (BGL), diabetes, insulin treatment, and obesity on 18F-FDG uptake in tumors and biodistribution in normal organ tissues.Methods 18F-FDG PET/CT was analyzed in 90 patients with BGL ranging from 50 to 372mg/dl. Of those, 29 patients were diabetic and 21 patients had received insulin prior to PET/CT; 28 patients were obese with a body mass index >25. The maximum standardized uptake value (SUVmax) of normal organs and the main tumor site was measured. Differences in SUVmax in patients with and without elevated BGLs, diabetes, insulin treatment, and obesity were compared and analyzed for statistical significance. Results Increased BGLs were associated with decreased cerebral FDG uptake and increased uptake in skeletal muscle. Diabetes and insulin diminished this effect, whereas obesity slightly enhanced the outcome. Diabetes and insulin also increased the average SUVmax in muscle cells and fat, whereas the mean cerebral SUVmax was reduced. Obesity decreased tracer uptake in several healthy organs by up to 30%. Tumoral uptake was not significantly influenced by BGL, diabetes, insulin, or obesity. Conclusions Changes in BGLs, diabetes, insulin, and obesity affect the FDG biodistribution in muscular tissue and the brain. Although tumoral uptake is not significantly impaired, these findings may influence the tumor detection rate and are therefore essential for diagnosis and follow-up of malignant diseases.